Atuação de incubadoras de empresas no desenvolvimento de uma indústria local de biotecnologia na área médica: estudo de caso da Fundação Biominas - Souza, Cláudio Vieira de (2005)
Despite the fact that the biotech industry is now facing a high progress stage, this sector deals with several issues that make difficult new ventures creation. New companies usually face the challenge of being scarce in resources, but constitute an important source of innovation, having an important rule on a local industry development. Therefore, it is essential for the biotech sector development, the presence of an environment, which has: low entrance barriers, incentives to productivity, to innovation and competitiveness. This essay analyzes the role played by the Fundação BIOMINAS business incubator, on the development of a medical biotech industry in Belo Horizonte Metropolitan area, trough a case study. The essay begins with a bibliographic research aiming to find premises about the actuation of a business incubator on regional industry development. First, it discusses: the factors that have influence on industry’s competitiveness; the influence of clustering on companies’ competitiveness; and the major environment’s influences on local industry development. Finally, it discusses the influences of business incubators on regional industry development. The results show the influences of Fundação BIOMINAS on the environment factors that guide to competitiveness and to the development of Medical Biotech Industry in Belo Horizonte area.